Distance Antimagic Labeling for Copies of Graph - Peter John; Bonardo Lubis; Kiki Ariyanti Sugeng (Jurnal Matematika UNAND, 2026)
Let G be a graph with vertex set V(G) and edge set E(G). Let f be a bijective function from the vertex set V(G) to the set {1,2,3,... ,|V(G)|} and weight of vertex v in V(G) is the sum of labels of all neighbors of vertex v. If there is no pair of vertices of V(G) have equal weight, then f is called a distance antimagic labeling and G is called a distance antimagic graph. Copies of graph G, denoted as nG is disjoint union of n graphs which each is isomorphic to G. In this paper, we present several results on distance antimagic labeling of copies of graph.